2019
DOI: 10.1177/2055668319844443
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive game design to evaluate social interaction effects on levels of physical activity among older adults

Abstract: Introduction Promoting active lifestyles among older adults can bring drastic benefits for their quality of life. The innovative mechanics of pervasive games – that mix real and virtual worlds – can further engage and motivate elderly people into that goal. Using social interaction as a study case, we designed and evaluated the feasibility of a pervasive game to investigate how game design elements can affect the levels of physical activity of older adults. Methods A mobile, location-based pervasive game was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Participants played a pervasive location-based mobile game called Shinpo, which, in free translation, means “steps of the gods” in Japanese. This game was first evaluated for its feasibility in Kyoto [ 19 ] and later used in a similar study in Brasília, Brazil [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants played a pervasive location-based mobile game called Shinpo, which, in free translation, means “steps of the gods” in Japanese. This game was first evaluated for its feasibility in Kyoto [ 19 ] and later used in a similar study in Brasília, Brazil [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility study and follow-up evaluations [ 17 , 22 ] suggested that these mechanics allowed players to feel more engaged in playing the game by working together with other people. We hypothesized that this setup would result in a greater positive effect on levels of physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Participants played a pervasive location-based mobile game called Trilhas [26,27]. This game has been previously evaluated for its feasibility and adaptability to allow for the testing of different design elements [28].…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility study and follow-up evaluations [27,28] suggested that these mechanics allowed players to feel more engaged in playing the game by working together with other people. We hypothesized that this setup would result in a higher positive effect on levels of physical activity.…”
Section: Methodsmentioning
confidence: 99%
“…Location-based AR mobile games differ from exergaming designed to promote PA mostly indoor; however, these AR games still demonstrate the potential to promote PA comparable to the recommended levels [ 10 ]. Further, AR mobile games might exert positive effects on individuals’ overall well-being as AR games predominately require the players to have some form of movement by combining gaming, walking, and exploring outdoor environments [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%